Acute abdomen in renocanalicular disease: Round table XXVI Uruguayan Congress of Surgery: coordinator Julio C Viola Peluffo - Viola Peluffo, Julio C; Clark, Omar; Delgado Pereira, Hugo; Durante Barbot, Arturo; Pereyra Bonasso, Jorge (Cirugía del Uruguay, 1976)
n the different urological clinics of the capital: Faculty of Medicine and Ministry of Public Health, we have verified a series of clinical cases that were seen first in the emergency services and in general surgical clinics, interpreted as pictures of acute abdomen of intraperitoneal origin treated as such and whose diagnosis was urinary etiology. The wish of this working group is to bring these clinical situations to your consideration.